Ombudsmen ComparedStaceyFrankOmbudsmen Compared. New York: Oxford University Press, 1978, 256 pp., $26.00 - Nielsen, Richard P. (Academy of Management Review, 1980)
The article reviews the book ?Ombudsmen Compared,? by Frank Stacey.